Enhancing nutritional status of stunted toddlers via supplementary feeding programs in Musi Banyuasin, 2023 - Dariusmansyah, Azmi; Najmah, Najmah; Wulandari, Anggun Restu; Maryadi, Maryadi; Mayasari, Yesi; Lestari, Ayu Seftiani; Sukaesi, Elvi; Marelinda, Cesa; Mazidawati, Mazidawati; Syamsia, Salwa; Budi, Iwan Stia; Safitri, Wulandari Dwi; Zalzabila, Anisah (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2025)
ABSTRACTBackground: Stunting is caused by long-term malnutrition. To reduce this problem, the government has launched the Supplementary Feeding Program (SFP). In Musi Banyuasin Regency, this program is called “BUNDA AS (Bunda dan Anak Sehat)”.Objective: To provide an overview and compare the nutritional status of stunted and wasted toddlers before and after the intervention of supplementary feeding program in Musi Banyuasin Regency in 2023.Materials and Methods: This study employed a quasi-experimental design with a pre-test and post-test approach. The human subjects in the study were 107 stunted and wasted toddlers aged 6-59 months, all from low-income families in the working area of Primary Health Care Center Musi Banyuasin. Anthropometric parameters were used to assess nutritional status. The Supplementary Feeding Program was implemented for 90 days. There are three main meals, one animal protein snack, and two additional supplementary feeding servings for toddlers aged 6-24 months each day. Paired t-tests was used to analyze the data and evaluate the effectiveness of SFP on the nutritional status of stunted and wasted toddlers.Results: The results showed significant changes in the nutritional status of toddlers based on the indicators of weight for Age (WAZ), height for Age (HAZ), as well as the ratio of weight to height (WHZ) before and after the BUNDA AS intervention. The paired t-test revealed a significant difference mean weight and height of toddlers (p = <0.0001).Conclusion: There was an effectiveness of SPF on the nutritional status of stunted and wasted toddlers before and after the intervention of the BUNDA AS program in Musi Banyuasin Regency in 2023.Keywords: BUNDA AS; nutritional status; stunting; toddlers